Non-State Actor's Strategy in Advocating the Movement to Reject Development Policy - Fajri, Hidayatul; Halawa, Historis Soterman; Wahyuni, Nila (JPAS (Journal of Public Administration Studies), 2023)
Geothermal is one of the potential renewable energy sources in Indonesia. This great potential makes the government try to develop geothermal energy development, one of which is in Mount Talang. However, the development received a rejection from the community, including non-state actors. This study looks at the strategy of the YLBHI Padang Legal Aid Institute in advocating the movement against the construction of geothermal energy-powered power plants. The studying conducted for 6 (six) months. This research design uses qualitative methods. The data sources we collect are interview data, observation results, official texts or policies, journal articles, websites on the internet, newspapers, social media, and youtube. The advocacy strategies carried out by LBH YLBHI Padang are; understanding strategic issues, building opinions and facts to the public, building coalition networks with civil society such as local communities, NGOs, students, national networks, and academics, designing goals and strategies as well as monitor and assess movements. The result of the advocacy carried out by LBH YLBHI Padang was the "temporary" suspension of constructing a geothermal energy power plant in Mount Talang. This research ends with research recommendations such as the need for inclusive stakeholder involvement in the formulation of development policies and 2) the need to grow civil society in the regions to become non-structural control for the government.